Considerations on design and implementation parameters of domestic wastewater treatment by subsurface flow constructed wetlands - Fadanelli,Lis Eveline Athaydes (2019)
ABSTRACT Constructed wetlands might be an alternative for communities away from urban centers and not served by a domestic wastewater treatment system. The purpose of this study was to provide instructions for the implementation of subsurface flow constructed wetland systems. To that end, we gathered information regarding the construction aspect, plants, and operational parameters used in systems which already operate in the country and the respective efficiency of these sets after previous treatment. The system in real scale proposed by Oliveira et al. (2005) was prominent among those that presented the highest efficiency. It was preceded by upflow anaerobic reactor built in brick, with macrophyte of the Typha genre, crushed stone at the entry and exit of the system, and sand in its intermediate portion. It required 1.04 m² surface area per inhabitant in humid temperate climate and hot summer, 1.71 m³ d-1 flow, and one-day hydraulic detention. The considerations presented here might help the construction of this kind of system, regarding dimensional and operational criteria.